2018
DOI: 10.1080/20469047.2017.1409454
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for the treatment of dysentery (shigellosis): a systematic review of the evidence

Abstract: Background: Shigella remains the primary cause of diarrhoea in paediatric patients worldwide and accounts for up to 40,000 deaths per year. Current guidelines for the treatment of shigellosis are based on data which are over a decade old. In an era of increasing antimicrobial resistance, an updated review of the appropriate empirical therapy for shigellosis in children is necessary, taking into account susceptibility patterns, cost and the risk of adverse events. Methods: A systematic review of the current pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
111
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(116 citation statements)
references
References 48 publications
3
111
0
2
Order By: Relevance
“…Williams and Berkley reported that resistance to the third generation of the cephalosporins due to increased number of the ESBL-producing bacteria has been increasingly prevalent in Asia, and suggested monitoring plans for such strains. 31 The relatively high rate of ESBL isolates in this study (59% and 46.1% for S. sonnei and S. flexneri, respectively) indicates a significant increase in the population of these superbugs and calls for urgent actions in developing new efficient alternatives for rapid detection, monitoring, and control/treatment strategies.…”
Section: Discussionmentioning
confidence: 73%
“…Williams and Berkley reported that resistance to the third generation of the cephalosporins due to increased number of the ESBL-producing bacteria has been increasingly prevalent in Asia, and suggested monitoring plans for such strains. 31 The relatively high rate of ESBL isolates in this study (59% and 46.1% for S. sonnei and S. flexneri, respectively) indicates a significant increase in the population of these superbugs and calls for urgent actions in developing new efficient alternatives for rapid detection, monitoring, and control/treatment strategies.…”
Section: Discussionmentioning
confidence: 73%
“…Shigella flexneri is a bacterium characterized by Gramnegative staining and its behaviour as a facultative anaerobe which is a member of the family, Enterobacteriaceae (Jin et al, 2002;Wei et al, 2003). Failure to introduce sufficient management of the infection may add some detrimental incidents that might prevent required recovery within normal times or might lead to lose life (Williams and Berkley, 2018). The disease initiated by these bacteria is well known for its million-based morbidity and mortality occurrence especially in children in poor-health system countries (Kotloff et al, 1999).The results in the current work revealed the presence of S.flexneri in the samples using the regular Lab techniques specific for the isolation of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The epithelial layers of the colon and rectum are the main targets for these bacteria leading to acute mucosal inflammation, severe tissue damage, abscess formation, ulceration, watery diarrhea, severe abdominal pain, and dysentery (Bennish, 1991;Taneja and Mewara, 2016). Lack of useful treatment may lead to the development of certain secondary health events such as septicemia, hemolytic uremic syndrome, pneumonia, rectal prolapse, arthralgia, seizures, toxic megacolon, intestinal perforation, electrolyte imbalance, and leukemoid reactions (Williams and Berkley, 2018).This disease is responsible of 1.1 million and over 164 million cases each year of mortalities and morbidities respectively; however, this disease attacks mostly children in countries with poor-health systems (Kotloff et al, 1999). The developing countries are known for the S. flexneri serotypes of 1b, 2a, 3a, 4a and 6; however, industrialized countries are known for the presence of 2a serotype in their patients (Kotloff et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Preventing shigellosis remains more than ever a public health priority. [98][99][100] Indeed, as recently reviewed, 101 there is a growing appreciation for the role of vaccines in confronting the problem of antimicrobial resistance, which includes the alarming emergence of multi-drug resistant Shigella strains. 98…”
Section: Implications For Vaccine Developmentmentioning
confidence: 99%